2019
DOI: 10.3390/ani9070455
|View full text |Cite
|
Sign up to set email alerts
|

Music Festival Makes Hedgehogs Move: How Individuals Cope Behaviorally in Response to Human-Induced Stressors

Abstract: Understanding the impact of human activities on wildlife behavior and fitness can improve their sustainability. In a pilot study, we wanted to identify behavioral responses to anthropogenic stress in an urban species during a semi-experimental field study. We equipped eight urban hedgehogs (Erinaceus europaeus; four per sex) with bio-loggers to record their behavior before and during a mega music festival (2 × 19 days) in Treptower Park, Berlin. We used GPS (Global Positioning System) to monitor spatial behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 47 publications
(53 reference statements)
2
14
0
Order By: Relevance
“…This behavioural pattern was observed regardless of the animal's sex. This finding indicates a certain behavioural stability of ALAN avoidance in hedgehogs, which is interesting given that significant interindividual differences in movement behaviour of hedgehogs were observed in response to a music festival in a park in Berlin [48]. Despite the overall preference for movement in less strongly illuminated areas, comparison of movement behaviour in relation to ALAN between the three study locations indicated that hedgehogs living in TE differed in their behaviour compared to the hedgehogs living in TP and TR.…”
Section: Discussionmentioning
confidence: 60%
“…This behavioural pattern was observed regardless of the animal's sex. This finding indicates a certain behavioural stability of ALAN avoidance in hedgehogs, which is interesting given that significant interindividual differences in movement behaviour of hedgehogs were observed in response to a music festival in a park in Berlin [48]. Despite the overall preference for movement in less strongly illuminated areas, comparison of movement behaviour in relation to ALAN between the three study locations indicated that hedgehogs living in TE differed in their behaviour compared to the hedgehogs living in TP and TR.…”
Section: Discussionmentioning
confidence: 60%
“…For example, in addition to potential nesting sites in patches of remnant natural or semi-natural vegetation, hedgehogs can access cavities beneath buildings, gardens sheds, or decking within residential gardens; urban residents may also supply artificial refugia in the form of homemade or commercially available “hedgehog houses” [ 7 , 31 ]. However, within each of these habitats/locations, hedgehogs are exposed to different levels of disturbance from humans or companion animals [ 39 , 40 ], road traffic [ 19 ], and artificial light [ 41 ] and sound. Similarly, temperatures within different microhabitats are likely to vary in relation to, for example, the density and composition of surrounding buildings and associated structures [ 31 , 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…In terms of behaviour parameters, there was no obvious general pattern as to how hedgehogs responded to different disturbances. Such high inter-individual behavioural variance in response to anthropogenic disturbance is an expression of behavioural flexibility and may contribute to successfully persist in challenging environments such as big cities [ 54 ]. However, behavioural flexibility also has the evolutionary cost that a chosen behavioural response may be inappropriate in that situation [ 79 ], and these are more likely if the anthropogenic disturbance is unequal to natural disturbances to which there may be an evolved response [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…The train and test dataset for the behaviour recognition were taken from a previous study. The whole procedure is described in [ 54 ]. By joining multiple Support Vector Machines (SVM), the selected behaviours were classified.…”
Section: Methodsmentioning
confidence: 99%